A scalable hydrogen propulsion system for civil transport aircraft - van Heerden, Albert S. J.; Sasi, Sarath; Ghelani, Raj; Sanders, Drewan S.; Roumeliotis, Ioannis (International Council of the Aeronautical Sciences (ICAS), 2022)
The aim of this research was to explore the application of engineering systems evolvability analysis techniques in devising potential scalable hydrogen propulsion systems for future civil transport aircraft. Baseline and derivative aircraft concepts were generated for a medium-sized long-range aircraft, with the derivative options having different levels of hydrogen incorporated in a dual-fuel arrangement (with separate hydrogen and kerosene turbofans), as well as potential turboelectric propulsion with boundary layer ingestion. Commonality between each baseline-derivative pair was then estimated, which could be used to predict the derivative development cost savings that could potentially be obtained when working from a specific baseline. The performance and cost results enabled different future scenarios to be explored. It was shown that developing the future concepts based on an existing state-of-the aircraft as baseline can offer considerable cost savings, as opposed to designing a clean sheet version. The importance of the baseline configuration selection in reducing the development cost for the different hydrogen configurations was also highlighted.
© The Author
Keywords: hydrogen propulsion; scalability; evolvability; dual-fuel; boundary layer ingestion; electric propulsion